Field notes contributed by Janet G. Greer, fall 1979 - Greer, Janet G.et al (1979)
List of birds and locations contributed by Janet G. Greer and observers Marg Graf, Tanya Bray, Babs Padelford, Sandra Kovanda, Ruth A. Gochenour and Ruth Gree. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1979. Epson - sheet feed/flatbed